Macroscopic on-site evaluation (MOSE) of specimens from solid lesions acquired during EUS-FNB: multicenter study and comparison between needle gauges - Mangiavillano, Benedetto; Frazzoni, Leonardo; Togliani, Thomas; Fabbri, Carlo; Tarantino, Ilaria; De Luca, Luca; Staiano, Teresa; Binda, Cecilia; Signoretti, Marianna; Eusebi, Leonardo H.; Auriemma, Francesco; Lamonaca, Laura; Paduano, Danilo; Di Leo, Milena; Carrara, Silvia; Fuccio, Lorenzo; Repici, Alessandro (Endoscopy International Open, 2021)
Background and study aims The standard method for obtaining samples during endoscopic ultrasonography (EUS) is fine-needle aspiration (FNA), the accuracy of which can be affected by the presence of a cytopathologist in endoscopy room (rapid on-site evaluation [ROSE]). With the introduction of fine-needle biopsy (FNB), macroscopic on-site evaluation (MOSE) of a acquired specimen has been proposed. Only a few studies have evaluated the role of MOSE and in all except one, a 19G needle was used. Our primary aim was to evaluate the diagnostic yield and accuracy of MOSE with different needle sizes and the secondary aim was to identify factors influencing the yield of MOSE.Patients and methods Data from patients who underwent EUS-FNB for solid lesions, with MOSE evaluation of the specimen, were collected in six endoscopic referral centers.Results A total of 378 patients (145 F and 233 M) were enrolled. Needles sizes used during the procedures were 20G (42 %), 22G (45 %), and 25G (13 %). The median number of needle passes was two (IQR 2–3). The overall diagnostic yield of MOSE was of 90 % (confidence interval [CI] 86 %–92 %). On multivariable logistic regression analysis, variables independently associated with the diagnostic yield of MOSE were a larger needle diameter (20G vs. 25G, OR 11.64, 95 %CI 3.5–38.71; 22G vs. 25G, OR 6.20, 95 %CI 2.41–15.90) and three of more needle passes (OR 3.39, 95 %CI 1.38–8.31).Conclusions MOSE showed high diagnostic yield and accuracy. Its yield was further increased if performed with a large size FNB needles and more than two passes.